Politik Pemerintahan Thailand Era Thaksin Shinawatra & Malaysia Era Anwar Ibrahim dalam Perspektif Illiberal Democracy serta Relevansinya dengan Indonesia - Lubis, Sahruddin; Zamharir, Hari (Populis : Jurnal Sosial dan Humaniora, 2024)
This research explores the practice of democratic politics in two countries that place constitutional monarchies in the life of the nation and state, namely Thailand and Malaysia during the Thaksin Sinawatra administration and Malaysia during the Dato Anwar Ibrahim era. The study was conducted using the perspective of Fareed Zakaria's illiberal democracy theory. This study applies a culture-context approach with content analysis methods and meta-analyses procedures. Data were collected from a number of scientific articles accessed through Google Scholar and books. The results of the study show the existence of the King of Thailand who still plays a minimal role, amidst changing values that indicate very liberal, thus potentially strengthening liberal democracy and further weakening the constitutional monarchy. Likewise, the King of the Malaysian still plays a minimal role, but in recent times—with the declining role of UMNO party, the King's role is very significant in the latest political crisis.  The finding of this study is that in the amidst of a wave of changing values that have the potential to further marginalize illiberal democracy in each country, the role of the king, especially in the case of Malaysia, is quite significant in overcoming the political crisis of power, especially as a mediating authority or authorized intermediary agency. Abstrak Penelitian ini mengkaji praktik politik demokrasi di dua negara yang menempatkan monarki konstitusional dalam kehidupan berbagsa dan bernegara di Asia, yakni Thailand pada era pemerintahan Thaksin Sinawatra dan Malaysia pada era Dato Anwar Ibrahim. Kajian dilakukan dengan menggunakan perspektif teori illiberal demokrasi dari Fareed Zakaria. Penelitian ini menerapkan pendekatan culture-context dengan metode analisis konten dan prosedur meta-analyses. Data dikumpulkan dari sejumlah artikel ilmiah yang diakses melalui Google Scholar dan buku-buku. Hasil penelitian menunjukkan bahwa ekistensi Raja Thailand masih berperan secara minimal, di tengah perubahan nilai-nilai yang mengindikasi amat liberal, sehingga potensial menguatkan demokrasi liberal dan makin memperlemah monarki konstitusional. Demikian pula dengan Raja Malaysia, masih berperan secara minimal, namun di masa belakangan—dengan jatuhnya The United Malays National Organization, peranan raja amat signifikan dalam kemelut politik mutakhir. Temuan penelitian ini menunjukkan bahwa di tengah gelombang perubahan nilai-nilai yang berpotensi makin meminggirkan illiberal democracy di masing-masing negara, peran raja, teristimewa dalam kasus Malaysia, cukup signifikan dalam mengatasi krisis politik kekuasaan, terutama sebagai mediating authority atau authorized intermediary agency.